Influence of temperatures of biochar derived from agro-waste onto polyester composite for improving the water effluent discharge - Siti Samahani, Suradi; Muhammad Fauzan Syafi, Mohamed Fouzi; Zainatul Umairah, Zainal Abidin; Dilaeleyana, Abu Bakar Sidik; Izirwan, Izhab; Nurul Izzati, Mohd Ismail; Hazirah, Bujang; Nurmina, Abdullah (EDP Sciences, 2024)
The biochar-based rice straw (RS) is the agro-waste from rice production which is one of the significant contributors to pollution. This study focused on altering RS biochar on polyester/polyvinylidene fluoride (RS-g-polyester) composites to improve the quality of water final effluent from industrial-based palm oil mills. Alteration of RS biochar-g-polyester composites was investigated at various RS calcination temperatures ranging from 300-900℃. The RS biochar-g-polyester composites were prepared using a dip-coating technique and characterized via spectroscopy (FTIR-ATR), Scanning Electron Microscopy (SEM-EDS), and tensile strength. Meanwhile, the performance of biochar RS-g-polyester composites was evaluated based on the pH, turbidity, and color removal of water effluent discharge. It was found that the biochar RS-g-polyester samples displayed different patterns in intensities and morphologies at different temperatures affecting the filtration of water effluent. Good interfacial compatibility of RS-g-polyester composite is also evidently seen via morphologies and mechanical properties. With consistent pH of waste effluent (8.83-8.89), the filtrate effluent discharge exhibits a significant reduction in color removal, 35% (~1150 ADMI), and turbidity, ~85% (0.9 8NTU) compared to initial water effluent discharge (~1800 ADMI). An increase in temperature has significantly improved the quality of water, thus it has potential use in the filtration of water treatment.